Analisis Pengaruh Atribut Produk, Kualitas Pelayanan dan Kepuasan Nasabah terhadap Loyalitas Nasabah pada PT Bank Rakyat Indonesia Tbk Kantor Cabang Samarinda 1 - Omar Dhanny; Erlinda Eka Nurmayanti (Jurnal EKSIS, 2022)
The researcher took the title "Analysis of the Effect of Product Attributes, Service Quality and Customer Satisfaction on Customer Loyalty at PT. Bank Rakyat Indonesia, Tbk. Samarinda Branch Office 1”, under the guidance of Mr. Dr. Sudarlan, S.E., M.T. as a supervisor I and Mr. Dr. H. Omar Dhanny, S.E., M. Kom. as Advisor II. This study aims to determine the effect of product attributes, service quality and customer satisfaction on customer loyalty at BRI branch Samarinda 1. The object used in this study is one of the companies in Samarinda, namely PT. Bank Rakyat Indonesia, Tbk. Samarinda Branch Office 1, using descriptive statistical methods. The sampling method in this study was accidental sampling and the data collection method used a questionnaire measured by a Likert Scale. The analytical tools used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, T test, F test, R test and R² test. The types of data used are primary data and secondary data. The number of research samples as many as 168 respondents. The results showed that partially Product Attributes, Service Quality, and Customer Satisfaction had a positive and significant effect on Customer Loyalty. Simultaneously Product Attributes, Service Quality, and Customer Satisfaction have a positive and significant effect on Customer Loyalty with a significance value of 0.000 < 0.05.